Devonia perrieri (Malard, 1903) (Bivalvia) found in situ on the holothurian Leptosynapta inhaerens (Müller, 1776) in Norway - Glenn A. Bristow; Per Johannessen; Bjørn Berland; Christoffer Schander (Fauna Norvegica, 2010)
The ectosymbiotic bivalve, Devonia perrieri, has earlier been found non-associated with its host in grab samples in Western Norway, but has never been found on its purported host, Leptosynapta inhaerens. Here we show it for the first time on its host, Leptosynapta inhaerens, in Norwegian waters. This confirms that the host in Western Norway is same as elsewhere in the bivalve’s distribution area.